Coexistence of nitrous oxide undersaturation and oversaturation in the surface and subsurface of the western Arctic Ocean. Issue 12 (28th December 2015) - Zhang, Jiexia; Zhan, Liyang; Chen, Liqi; Li, Yuhong; Chen, Jianfang
Abstract: The nitrous oxide (N2 O) distributions in a shelf‐slope‐basin section from the Chukchi Sea shelf to the Chukchi Abyssal Plain (CAP) in the western Arctic Ocean were observed for the first time during the fourth Chinese National Arctic Research Expedition (4th CHINARE) in late August 2010. The N2 O concentrations were 11.4–16.9 nmol L −1, corresponding to saturation values of 92–118% in the surface water. In the surface, biological factor was negligible to N2 O production, and physical process dominated the surface N2 O distribution. The N2 O undersaturation may be the result of dilution by sea ice meltwater. The oversaturation may be caused by the diffusing of N2 O‐rich shelf bottom water. Below the surface, N2 O concentrations ranged from 11.4 to 21.4 nmol L −1 . On the Chukchi Sea shelf, N2 O concentrations increased from the surface to the near‐bottom water, indicating sediment N2 O produced by nitrification or denitrification emission may be a significant source. The subsurface maxima in the upper halocline layer (UHL) may receive partial contribution from nitrification production but was primarily caused by the spreading of shelf water. Key Points: N2 O undersaturation was observed in the surface water of the western Arctic Ocean Sediment may be a significant N2 O source of shelf water Lateral spreading of shelf water primarily caused N2 O maxima in the UHL